1988
DOI: 10.1002/cne.902750408
|View full text |Cite
|
Sign up to set email alerts
|

Cytoarchitectonic analysis of the SDN‐POA of the intact and gonadectomized rat

Abstract: The densely staining group of cells referred to as the sexually dimorphic nucleus of the preoptic area (SDN-POA) is greater in volume in the male than in the female rat. Because we and others have reported absolute volumes that have been consistent within individual studies but that vary considerably, we characterized the SDN-POA by describing its morphology with respect to the cytoarchitectonic divisions of the medial preoptic nucleus (MPN) in intact and gonadectomized rats. We report three major findings: th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(55 citation statements)
references
References 32 publications
3
52
0
Order By: Relevance
“…Theses lateral cells therefore tend to be larger in males than in females [102] since males on average have higher circulating concentrations of testosterone in the blood [18]. The volume of the entire POM and the size of neurons in the lateral part of this nucleus thus provide a clear morphological signature of testosterone action in the brain contrary to what is observed for sexually dimorphic brain areas in the preoptic region in other species such as the SDN-POA of rats [11,73,143] but similar to observations reported concerning the gerbil SDA [52,53,55] or the rat MPN [41,42]. Interestingly, the effects of testosterone on the neuronal size are more pronounced in the lateral part of the POM than in the medial part of the nucleus adjacent to the third ventricle [102].…”
Section: The Preoptic Neuronal Circuit Controlling Male Sexual Behavisupporting
confidence: 70%
See 2 more Smart Citations
“…Theses lateral cells therefore tend to be larger in males than in females [102] since males on average have higher circulating concentrations of testosterone in the blood [18]. The volume of the entire POM and the size of neurons in the lateral part of this nucleus thus provide a clear morphological signature of testosterone action in the brain contrary to what is observed for sexually dimorphic brain areas in the preoptic region in other species such as the SDN-POA of rats [11,73,143] but similar to observations reported concerning the gerbil SDA [52,53,55] or the rat MPN [41,42]. Interestingly, the effects of testosterone on the neuronal size are more pronounced in the lateral part of the POM than in the medial part of the nucleus adjacent to the third ventricle [102].…”
Section: The Preoptic Neuronal Circuit Controlling Male Sexual Behavisupporting
confidence: 70%
“…However, these studies did not determine whether neurons in the preoptic region involved in copulatory behavior are limited to the MPN. Neurochemical studies and analysis of connectivity have revealed clearly defined sub-regions within this nucleus (medial, central and lateral parts; e.g., [41,128,129]) but the specific implication of these sub-regions in the control of different aspects of male sexual behavior is still not well understood. A central subdivision of the MPN in rats that is larger in volume in males than in females was shown to be sexually differentiated by the action of steroids during embryonic life (the sexually dimorphic nucleus of the mPOA or SDN-POA; [41,72]).…”
Section: The Preoptic Neuronal Circuit Controlling Male Sexual Behavimentioning
confidence: 99%
See 1 more Smart Citation
“…One possible limitation of these volumetric findings is that we examined adult, gonadally intact animals. Circulating levels of gonadal steroid hormones in adulthood affect neuronal size and͞or the volume of cell groups in several neural regions (33)(34)(35) and could have affected volume measures here. However, we are not aware of any reports of circulating hormones influencing AVPV volume, and a sex difference in BNSTp volume of guinea pigs is not altered by adult gonadectomy (36).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these results suggest that the MPO + PAG + RVM projection constitutes a functional pathway. This circuit may coordinately regulate neuroendocrine, motor, and autonomic adjustments necessary for the elaboration of sexual behaviors.Key words: reproduction; antinociception; cardiovascular regulation; brainstem; sexual behavior; immunohistochemistryThe medial preoptic area (h/[PO) is a sexually dimorphic structure Simerly et al, 1984;Bloch and Gorski, 1988) that plays a pivotal role in sexual behavior and neuroendocrine function (Lisk, 1966;Powers and Valenstein, 1972;Pfaff and Sakuma, 1979;Hansen et al, 1982;Arendash and Gorski, 1983;Kalra and Kalra, 1983;Docke et al, 1984;Sachs and Meisel, 1988;Simerly et al, 1990;DonCarlos et al, 1991;Takeo et al, 1993;Hoshina et al, 1994). We recently reported that MPO robustly innervates the midbrain periaqueductal gray (PAG) (Rizvi et al, 1992) and terminates in discrete, longitudinally organized columns running through the rostrocaudal axis of PAG.…”
mentioning
confidence: 99%